Sustainable Travel : The essential guide to positive-impact adventures - Tuppen, Holly, ....- (London : White Lion Publishing, 2021)
Sustainable Travel offers practical and achievable advice for those who want to make a difference in the way we experience the world, filled with great tips, tricks and ideas to help you explore the planet in a sustainable way! Having travelled around the world without flying, sustainability expert Holly Tuppen knows a thing or two about low-carbon and positive-impact adventures. Here, she shares what she's learnt from over a decade of responsible travels.
Keywords: Duurzaam Reizen; Duurzaam toerisme; Reizen; Toerisme